Studying the influence of supply pulse duration on the phase composition of iron oxides obtained by the plasma-dynamic method; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Shanenkov I. I. Ivan Igorevich; Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Gukov M. I.; Shanenkova Yu. L. Yuliya Leonidovna (2021, 2021)
Title screen